PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, TERHADAP BELANJA DAERAH DAN DANA BAGI HASIL SEBAGAI PEMODERASI PEMERINTAH KABUPATEN / KOTA DI PROVINSI JAWA BARAT PERIODE TAHUN 2010/2014 - Untung, Joko; Widyastuti, Tri; Suyanto, - (E-Journal Widya Ekonomika, 2018)
Regional generated revenues is the main source of regional funding, therefore the ability to implement the economic measure of the magnitude of the contribution made by the Regional generated revenues of the budget, the greater the contribution that can be provided by the Regional generated revenues of the budget means less dependence of local governments on central government and. The objective of the research was to find out the influence of PAD (Regional Generated Revenues), DAU (General Allocation Fund), and DAK (Specific Allocation Fund) and Sharinf Funds as moderating variable on the relationship between PAD, DAU, DAK with regional expenditure. The sample used in this study were 26 Districts / Towns comprises were determined by purposive sampling method. The criteria used in determining the sample of the Regency / City Budgets publish consistently from 2010-2014. The data used in this research is secondary data.The results showed that the PAD, DAU and DAK simultaneously affect the regional expenditure. Partially PAD and DAU effect on regional expenditure while DAK has no effect on regional expenditure. The results of the research with moderation regression analysis (MRA) showed that DBH not moderating variables strengthen or weaken the relationship PAD, DAU, DAK with regional expenditure.